H2 production in underground coal gasification with pretreatment by non-focusing microwave - Feng, Lele; Dong, Jie; Li, Haidong; Sun, Jiaxuan (Frontiers in Chemistry, 2025)
IntroductionUnderground coal gasification (UCG) faces challenges in product quality control and combustion stability. While microwave heating enhances coal seam heat/mass transfer efficiency, existing studies prioritize focused microwaves, overlooking non-focusing radiation.MethodsTwo microwave systems were used to treat coal in this paper. Gasification experiments were conducted on the treated coal. Meanwhile, its microscopic properties were tested by industrial analysis, mercury pressure method and Fourier Transform Infrared Spectroscopy (FTIR) method.ResultsFirstly, non-focusing microwaves achieve more stable gasification despite comparable gas production durations. Secondly, focused microwaves enhance energy absorption and reduce coal moisture, while non-focusing radiation alters coal composition by increasing volatile matter and decreasing fixed carbon. Finally, non-focusing modes improve coal combustibility and reduce particulate emissions with minimal environmental impact, contrasting with focused microwaves limited ecological effects. Both methods similarly reduce coal porosity and pore volume.DiscussionThis work compares gasification performance and physicochemical changes under both modalities, revealing three critical differences. These results provide critical insights for optimizing microwave-assisted UCG systems.